Goat Medicine and Surgery - Harwood, David; Mueller, Karin; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Key features: Covers both goat medicine and surgery. Covers basic anatomy, commons breeds and husbandry. Includes new and emerging diseases. Goats are one of the most widely kept domestic animals globally, mainly as a result of the relative ease with which they can be kept and the obvious benefits provided to those who keep them. Goat Medicine and Surgery describes the key diseases that can have an impact on goat health and welfare worldwide, providing information on diagnosis, treatment, prognosis, management and control. Covers basic anatomy, common breeds and husbandry. Divided into chapters covering each body system. Offers the common differential diagnoses, followed by the specific diagnosis and recommended treatments. Covers a wide range of disorders, including new and emerging diseases. Modern goat keeping gives us a full spectrum of activity from nomadic tribes moving with their animals, to the range-keeping in Australia, to units fattening goat kids for meat and to intensive goat dairy production systems.$1!# (BAlongside these production systems are those in which goats are kept in small numbers as a hobby, as pets and at public attractions. This book deals with the diseases and challenges impacting all kinds of goats and their owners. It will be invaluable to veterinarians in practice and training, animal scientists and agricultural advisors, as well as scientists interested in animal welfare.s
Chapter 1: Introduction: World goat population and reasons they are kept. Common Breeds. Goat Biology. Husbandry. Chapter 2: Reproductive System: Normal structure & function. Breeding management. Female reproductive tract diseases. Causes of foetal loss / abortion. Male reproductive tract diseases. Chapter 3: Pregnancy and Parturition: Pregnancy diagnosis. Normal kidding. Dystocia. Caesarean section. Pseudopregnancy / cloudburst. Chapter 4: Neonatology: Neonatal kid care. Neonatal disorders. Disbudding. Castrating. Supernumerary teats. Chapter 5: Alimentary Tract and Abdomen: Examination. Non-infectious disease. Infectious disease. Surgical conditions / procedures. Chapter 6: Respiratory System: Examination. Non-infectious disease. Infectious disease. Chapter 7: Cardiovascular Disease and Disorders of the Haematopoietic System: Examination. Cardiovascular disorders. Haematopoietic disorders including lymphatic system. Chapter 8: Nervous System Disorders: Examination. Non-infectious disease (CNS) Non-infectious disease (peripheral) Infectious disease. Chapter 9: Musculoskeletal Disease including Foot Disorders: Examination. Non-infectious disease (including fracture management) Infectious disease. Chapter 10: Urinary Tract Disease: Examination. Non-infectious disease. Infectious disease. Surgical procedures. Chapter 11: Skin Diseases: Examination. Non-infectious disease. Infectious disease. Surgical procedures and wound management. Dehorning / disbudding. Chapter 12: Mammary Gland: Examination. Non-infectious disease. Infectious disease. Surgical procedures. Chapter 13: Sensory Organ Disease: Diseases of the eye & surgical procedures. Diseases of the ear. Chapter 14: Metabolic Diseases. Chapter 15: Trace Element Disorders. Chapter 16: Poisoning. Chapter 17: Emerging and Exotic Diseases: Tuberculosis. Bluetongue. Schmallenberg. FMD. Chapter 18: Anaesthesia and Analgesia, Fluid Therapy and Euthanasia. Chapter 19: Post Mortem Examination and Sampling. Appendix 1: References Ranges: Appendix 2: Pharmacology. Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Goats -- Diseases; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Goat Diseases; Electronic books